Role of C- reactive proteins and liver function tests in assessing the severity of dengue fever - Akash Khetpal; Ansab Godil; Muhammad Tanveer Alam; Inam ul Haq Muhammad Makhdoom; Arsalan Majeed Adam; Muhammad Saad Ali Mallick; Mohammad Abubakar Abbas; Abdul Haseeb Abbas; Syed Saboor Hasan; Asim Shaikh; Hassan Ahmed; Rohan Kumar Ochani (Journal of the Pakistan Medical Association, 2020)
Objective: To determine whether C-reactive protein and liver function tests can serve as severity markers for dengue fever. Methods: The cross-sectional study was conducted in 2015-16 in Karachi and comprised patients with dengue fever visiting a tertiary care hospital. World Health Organisation classifications 1997 and 2009 were used to categorise patients according to clinical signs and symptoms. Receiver Operating Characteristics curve was used to determine discriminative ability and optimum cut-off value of biochemical markers. Comparisons were done through one-way analysis of variance using SPSS 17. Results: Of the 218 patients, 133(61%) were males and 85(39%) were females. The overall mean age was 35.07+15.96 years. Levels of C-reactive protein and total bilirubin were significantly higher for dengue haemorrhagic fever compared to dengue fever; dengue shock syndrome compared to dengue fever; dengue shock syndrome compared to dengue haemorrhagic fever; and dengue shock syndrome compared to dengue fever / dengue haemorrhagic fever (p<0.05 each). Levels of alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase were significantly higher for dengue shock syndrome compared to dengue fever; dengue shock syndrome compared to dengue haemorrhagic fever; and dengue shock syndrome compared to dengue fever / dengue haemorrhagic fever (p<0.05 each). Levels of C-reactive protein, total bilirubin, alanine aminotransferase and alkaline phosphatise in patients with severe dengue were significantly higher compared to non-severe dengue. Conclusion: C-reactive protein and liver function tests were found to be effective biochemical markers in assessing dengue fever severity.